Prescription Redemption and Price-Related Decisions among Hypertensive Patients in Community Pharmacies in Surabaya - Deapsari, Fani; Rafif Fidaus, Favian; Charis Aqsha, Aulia; Almaulidia Rahman, Nabila (Brawijaya University, 2026)
Introduction: Hypertension remains a major public health problem worldwide. Prescription redemption is a critical early step to medication adherence. Objectives: This study examined prescription redemption behavior, price-related decision-making, and pharmacist consultation behavior among hypertensive patients attending community pharmacies in Sawahan District, Surabaya, Indonesia. Methods: A cross-sectional survey was conducted among 258 adult patients using a structured behavioral questionnaire covering sociodemographic characteristics, clinical profile, prescription redemption patterns, price attention, generic substitution requests, and pharmacist consultation behavior. Results: Most participants reported visiting a pharmacy after physician consultation (82.9%); however, only 46.1% consistently redeemed all medicines listed on the prescription. High price attention was reported by 64.0% of participants, whereas only 16.7% frequently requested generic alternatives. Pharmacist consultation was common (77.5%), particularly among unemployed and newly diagnosed patients. In bivariate analysis, complete prescription redemption was associated with longer duration of hypertension, willingness to pay out of pocket, and not purchasing medicines outside the prescription. Conclusions: These findings suggest that cost awareness does not automatically lead to patient-initiated generic substitution and indicate a need for proactive pharmacist counseling that explicitly addresses affordability, complete redemption, and appropriate generic options.